Advanced solar cell materials, technology, modeling, and simulation - Fara, Laurentiu; Yamaguchi, Masafumi, 1946- (Engineering Science Reference, 2013)
"Featuring a premiere cast of the leading photovoltaic scientists from around the globe, this book addresses the fundamental challenges in the field and examines the basic fundamental limitation of photovoltaic conversion"--Provided by publisher.
Keywords: Photovoltaic cells -- Materials.; Solar cells -- Materials.; Photovoltaic cells -- Design and construction.; Solar cells -- Design and construction.; Photovoltaic power generation.; elektronické knihy; electronic books